Human security issues of deep wells retraining - Zákányiné Mészáros, Renáta; Zákányi, Balázs (International Journal of Engineering and Management Sciences, 2019)
Nowadays, in the world's energy production structure, fossil fuels dominate and at the same time cause a number of environmental problems. Comparing the use of conventional fossil fuels with geothermal energy, this kind of energy production is extremely beneficial, as there are no pollutants and a renewable energy source. Moreover, if we want to compare geothermal energy with other renewable energy sources (such as wind energy, solar energy, etc.), much of the benefits can also be attributed to geothermal energy becouse it is a stable energy source and the area requirement is low. Due to these extremely favorable properties, the study of the applicability of geothermal energy is gaining ground in renewable energy sources. In addition, it is well known that there are approximately 20 to 30 million abandoned oil wells in the world, plus sealed wells for other purposes, and the final number may be much larger. In the case of abandoned oil wells, the escaping residual oil may be a problem, which can lead to significant environmental problems. Taking these factors into account, research on the recyclability of abandoned wells for geothermal purposes becomes a target for more and more research topics around the world. It is interesting to note that a significant part of the publications are concerned with examining the technological potential of energy utilization, studying heat transport processes, and generating general, energetic or economical evaluations. A publication of a kind that would have evaluated the safety of recyclable abandoned wells in publishing databases was limited. It is therefore an important question that the abandoned wells, from the point of view of human security and environmental protection. How can they be reactive, how can the new technological elements be built up and how much human security factors of the newly created system are affected by the existing elements?